Synthesis, structure and properties of three 1D d10 metal–organic coordination polymers with 5-amino-2,4,6-triiodoisophthalic acid - Zhang, L.; Wei, Y.; Zhong, Y.Q.; Chang, Y.; Meng, Q.H.; Ng, S.W.; Zhang, K.L. (Elsevier, 2015)
he work presents an further investigation on the coordination chemistry of 5-amino-2,4,6-triiodoisophthalic acid (H2ATIBDC) and reveals the significant function of weak interactions in constructing the resultant supramolecular networks. Reactions of H2ATIBDC with the d10 metal ions [Zn(II) and Cd(II)] in the presence of varied N-donor auxiliary imidazole ligands at ambient condition yield three new 1D metal-organic coordination polymers (CPs): {[Cd(ATIBDC)(biim)]·2H2O}n (1), {[Zn(ATIBDC)(biim)]·3H2O}n (2) and [Cd(ATIBDC)(bbi)]n (3) [biim = 2,2′-biimidazole, bbi = 1,1′-(1,4-butanediyl)bis(imidazole)], which are characterized by elemental analysis, IR spectroscopy, thermogravimetry and single crystal X-ray diffraction measurements. Generally, these three complexes display 1D ATIBDC2--bridged coordination arrays. Extended 3D supramolecular network architectures are further constructed through the weak secondary interactions: aromatic stacking, halogen bonding and hydrogen bonding. It should be interesting to emphasize that the C-I...π halogen bonding plays significant role in the supramolecular assembly of 3. An acyclic trimeric water cluster (D3 chain) was observed and discussed in 2. Thermal stabilities of 1, 2 and 3 have been studied. The fluorescent properties of 1, 2 and 3 have been investigated in the solid state. Compounds 1 and 2 show completely reversible dehydration-rehydration behaviors, which reveal that 1 and 2 may possibly be used as water adsorbents.